Scalp Basal Cell Carcinoma: Review of 2, 202 Cases. Issue 7 (July 2016) - Cho, Matthew; Lee, Jaein; James, Craig L.; Marshman, Gillian; Huilgol, Shyamala C.
Abstract : BACKGROUND: Increases in the incidence of basal cell carcinoma (BCC) in women, younger age groups and in aggressive scalp subtypes in younger women have been reported. OBJECTIVE: To describe lesion and patient characteristics in scalp BCC. MATERIALS AND METHODS: Retrospective audit of scalp BCCs from 3 pathology laboratories in Adelaide, South Australia, January 2009–December 2013. RESULTS: Scalp BCC was 2.6% of all BCC. Of 2, 202 patients with scalp BCC, 62% were male and 78% were >60 years. Histologic subtypes included nodular (55%), mixed (30%), and superficial (8%). The concordance between biopsy and excision was 83% for division into nonaggressive and aggressive subtypes. The incomplete excision rate was 16%. Aggressive subtypes were larger and had perineural invasion (PNI) in 8.5% and incomplete excision in 26%. CONCLUSION: Basal cell carcinoma on the scalp was less common. Men and the elderly had the majority of cases, with no predilection for women, including aggressive histologic subtypes in younger women. Aggressive subtypes were associated with increased size, incomplete excision, and PNI. A preliminary biopsy assisted division into aggressive and nonaggressive histologic subtypes. Incomplete excision rates were higher and increased in aggressive histologic subtypes and PNI. Mohs surgery or wider margins are suggested in these cases.